penggunan Penggunaan Metode Numbered Heads Together (NHT) Untuk Meningkatkan Hasil Belajar Matematika Materi Bilangan Cacah Kelas IV Di UPTD SD Negeri 1 Kota Raman - Fajar Sidiq; Bambang Ariyanto; Pixyoriza (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The low mathematics learning outcomes of fourth-grade students at UPTD SD Negeri 1 Kota Raman are attributed to the dominance of teacher-centered instructional methods, which limit student engagement during the learning process. This study aims to improve learning outcomes through the implementation of the Numbered Heads Together (NHT) method on the topic of whole numbers. The research employed a Classroom Action Research (CAR) design conducted over two cycles, each consisting of two sessions. The research subjects were 29 students. The findings indicate a significant improvement in student learning outcomes. In the first cycle, the average score was 60.4 with a mastery level of 65.5%. After the instructional improvements in the second cycle, the average score increased to 85.5 with a mastery level of 86%. The difference in mastery levels between the two cycles reached 20.5%. Based on these results, it can be concluded that the implementation of the Numbered Heads Together (NHT) method is effective in enhancing mathematics learning outcomes among fourth- grade students at SDN 1 Raman Utara in the 2025/2026 academic year